1999
DOI: 10.1063/1.371247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preirradiation and thermal annealing on photoinduced defects creation in synthetic silica glass

Abstract: Defect structure of carbon rich a -SiC:H films and the influence of gas and heat treatments Effects of preirradiation by ArF-excimer laser and thermal annealing on photoinduced defects creation in synthetic silica glass were investigated by optical absorption measurements. It has been confirmed that the durability for ArF-excimer laser irradiation can be improved by the preirradiation followed by annealing. The absorption spectra strongly suggest that a dominant role of the preirradiation should be to assist r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It has been well known that there are four basic point defects in silica glasses, which are E' centers, NBOHCs, peroxy radicals, and self-trapped holes. These defects can be decreased when the synthetic silica was treated by pre-irradiation and subsequent thermal annealing [9,10]. Thermal treatment process also can produce various defects, which are induced typically in optical fibers [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been well known that there are four basic point defects in silica glasses, which are E' centers, NBOHCs, peroxy radicals, and self-trapped holes. These defects can be decreased when the synthetic silica was treated by pre-irradiation and subsequent thermal annealing [9,10]. Thermal treatment process also can produce various defects, which are induced typically in optical fibers [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Griscom has shown that the defect centers can be decreased when the synthetic silica was irradiated by rays and then annealing [9]. Saito glass [10]. They found that defect centers induced by ultraviolet (UV) light in bulk silica glass can be reduced by pre-irradiation and thermal annealing.…”
Section: Introductionmentioning
confidence: 99%